2011
DOI: 10.1175/2010jpo4559.1
|View full text |Cite
|
Sign up to set email alerts
|

Equatorward Pathways of Solomon Sea Water Masses and Their Modifications

Abstract: International audienceThe Solomon Sea is a key region of the southwest Pacific Ocean, connecting the thermocline subtropics to the equator via western boundary currents (WBCs). Modifications to water masses are thought to occur in this region because of the significant mixing induced by internal tides, eddies, and the WBCs. Despite their potential influence on the equatorial Pacific thermocline temperature and salinity and their related impact on the low-frequency modulation of El Niño-Southern Oscillation, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 34 publications
3
50
0
Order By: Relevance
“…Site MD05-2925 (9.3 • S, 151.5 • E, water depth 1661 m) is located at the northern slope of the Woodlark Basin in the Solomon Sea, which is the passage of surface and subsurface water masses between low-and middle-latitude South Pacific Ocean gyre and cross equatorial currents (Grenier et al, 2011;Melet et al, 2011) (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Site MD05-2925 (9.3 • S, 151.5 • E, water depth 1661 m) is located at the northern slope of the Woodlark Basin in the Solomon Sea, which is the passage of surface and subsurface water masses between low-and middle-latitude South Pacific Ocean gyre and cross equatorial currents (Grenier et al, 2011;Melet et al, 2011) (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…The models were validated in the Solomon Sea and at the equator [ Melet et al ., ; Grenier et al ., ] and their performances will not be shown in this study, for the sake of clarity and paper length. Here we first evaluated the ¼° OGCM performance in the southwestern Pacific against the CARS climatology [ Ridgway et al ., ] (Figures a and b).…”
Section: Tools and Experiments Definitionsmentioning
confidence: 98%
“…In their modeling study, Melet et al . [] showed that the temperature and salinity of the waters transiting through the Solomon Sea were in better agreement with observations when vertical mixing induced by the dissipation of internal tides was parameterized in their model. Strong diapycnal mixing in the Solomon Sea mostly explained the erosion of the high salinity of upper thermocline water [ Donguy , ], and its export toward surface and deeper layers.…”
Section: Introductionmentioning
confidence: 99%